Simplified process for the production of anti–CD19-CAR–engineered T cells - Tumaini, Barbara; Lee, Daniel W.; Lin, Tasha; Castiello, Luciano; Stroncek, David F.; Mackall, Crystal; Wayne, Alan; Sabatino, Marianna (Cytotherapy (Oxford, England), 2013)
Adoptive immunotherapy with the use of chimeric antigen receptor (CAR)-engineered T cells specific for CD19 has shown promising results for the treatment of B-cell lymphomas and leukemia. This therapy involves the transduction of autologous T cells with a viral vector and the subsequent cell expansion. We describe a new, simplified method to produce anti-CD19-CAR T cells. T cells were isolated from peripheral blood mononuclear cell (PBMC) with anti-CD3/anti-CD28 paramagnetic beads. After 2 days, the T cells were added to culture bags pre-treated with RetroNectin and loaded with the retroviral anti-CD19 CAR vector. The cells, beads and vector were incubated for 24 h, and a second transduction was then performed. No spinoculation was used. Cells were then expanded for an additional 9 days. The method was validated through the use of two PBMC products from a patient with B-cell chronic lymphoblastic leukemia and one PBMC product from a healthy subject. The two PBMC products from the patient with B-cell chronic lymphoblastic leukemia contained 11.4% and 12.9% T cells. The manufacturing process led to final products highly enriched in T cells with a mean CD3+ cell content of 98%, a mean expansion of 10.6-fold and a mean transduction efficiency of 68%. Similar results were obtained from the PBMCs of the first four patients with acute lymphoblastic leukemia treated at our institution. We developed a simplified, semi-closed system for the initial selection, activation, transduction and expansion of T cells with the use of anti-CD3/anti-CD28 beads and bags to produce autologous anti-CD19 CAR–transduced T cells to support an ongoing clinical trial.